My 40-Year History with Cronobacter/Enterobacter sakazakii – Lessons Learned, Myths Debunked, and Recommendations - Farmer, John J. (Frontiers in Pediatrics, 2015)
Much has been learned about organism in the Cronobacter/Enterobacter sakazakii complex since I first named and described Enterobacter sakazakii in 1980. However, there are still wide knowledge gaps. One of the most serious is that are still many uncertainties associated with assessing the public health risk posed by these bacteria, particularly in neonatal meningitis. Over the last few decades, Cronobacter contamination of commercial powdered infant formula products has apparently been reduced, but it is still an ongoing problem. The powdered infant formula industry still cannot produce powdered formula that is free of bacterial contamination with Cronobacter, other Enterobacteriaceae, other pathogenic bacteria, and other microorganisms. Until this happens, infants and other will be at risk of becoming infected when they ingest contaminated formula.